Convection in the liquid at droplet squeezing out of the capillary - Misyura S. Ya. Sergey Yakovlevich; Strizhak P. A. Pavel Alexandrovich; Volkov R. S. Roman Sergeevich; Morozov V. S. Vladimir (2023, 2023)
Title screen